Down-regulated miR-15a mediates the epithelial–mesenchymal transition in renal tubular epithelial cells promoted by high glucose. Issue 8 (3rd August 2014) - Sun, Tingli; Yang, Jun; Dong, Wenpeng; Wang, Ruiyan; Ma, Peilong; Kang, Ping; Zhang, Hongbo; Xie, Changying; Du, Juan; Zhao, Lijie
Abstract: High glucose (HG) has been reported to be associated with renal dysfunction. And one potential mechanism underlining the dysfunction is the epithelial–mesenchymal transition (EMT) of renal tubular epithelial cells. Present study showed that EMT was induced in the HG-treated renal tubular epithelial cells by promoting the expression of mesenchymal phenotype molecules, such as α-SMA and collagen I, and down-regulating the expression of epithelial phenotype molecule E-cadherin. Moreover, we have identified the down-regulation of miR-15a which was accompanied with the HG-induced EMT. And the miR-15a overexpression inhibited the α-SMA, collagen I expression, and the promotion of E-cadherin expression by targeting and down-regulating AP4 which was also significantly promoted by the HG in the renal tubular epithelial cells. Thus, this study revealed that the weakening regulation on the AP4 expression by miR-15a might contribute to the HG-induced EMT in the renal tubular epithelial cells. Graphical abstract: : miR-15 Mimics reversed the HG-induced EMT in renal tubular epithelial cells in vitro